STRUKTUR PENYAJIAN EMPAT LAGU PADA MUSIK DHOL DALAM PROSESI RITUAL TABUT DI PROVINSI - Relly Dyona; Syeilendra Syeilendra; Marzam Marzam (SENDRATASIK UNP, 2014)
Abstract This article was intended to describe the Presentation Structure of the Four Songs in the Dhol Music in the Tabut Ceremony in Provinsi Bengkulu. This was a qualitative research which used descriptive method. The data was collected through library study, observation, interview, and documentation. The data analysis was done by classifying the data based on the conceptual framework. The result of the research revealed that the presentation structure of the four songs in Dhol music was (1) the ritual of Ambik Tanah, Duduk Penja and Menjara accompanied by Suweri, Melalu and Tamatam songs, (2) the ritual of Meradai accompanied by Suwena song, (3) the ritual of Arak Penja, Arak sorban, Gham and Arak Gedang without the accompaniment of dhol music, and (4) the ritual of Tabut Naik Pangkek and Tabut Tebuang accompanied by Suweri, Suwena and Tamatam songs. Kata kunci : Stuktur, Penyajian, Empat, Lagu